2018
DOI: 10.1002/celc.201800657
|View full text |Cite
|
Sign up to set email alerts
|

Highly Dispersed Cu−NX Moieties Embedded in Graphene: A Promising Electrocatalyst towards the Oxygen Reduction Reaction

Abstract: Transition metal–carbon–nitrogen catalysts for the oxygen reduction reaction (ORR) are promising and challenging. Cu is a potential transition metal to form efficient ORR catalysts for fuel cells. Herein, a facile method is developed to synthesize a highly dispersed Cu−NX and N‐doped graphene (Cu−N−G) catalyst. The Cu−N−G catalyst shows a half‐wave potential (E1/2) of 0.859 V, which is comparable to the commercial Pt/C catalyst (0.856 V), and is among the best compared with the previously reported Cu‐based mat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 32 publications
(15 citation statements)
references
References 41 publications
0
15
0
Order By: Relevance
“…These values are much better than those of Cu NPs and SNGF, and are comparable to those of other Cu based catalysts (Table S1). The Koutecky‐Levich (K−L) plots at different potentials suggest good linearity for all electrodes (Figure S19), from which the values of electron transfer number ( n ) are determined (Figure S21a) . Accordingly, the n value for Cu clusters is 3.8, which is higher than those for Cu NPs (3.4) and SNGF (2.7).…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…These values are much better than those of Cu NPs and SNGF, and are comparable to those of other Cu based catalysts (Table S1). The Koutecky‐Levich (K−L) plots at different potentials suggest good linearity for all electrodes (Figure S19), from which the values of electron transfer number ( n ) are determined (Figure S21a) . Accordingly, the n value for Cu clusters is 3.8, which is higher than those for Cu NPs (3.4) and SNGF (2.7).…”
Section: Resultsmentioning
confidence: 94%
“…The current density decreases only 0.5 % after 20000 s for the Cu clusters/SNGF, while the Pt/C catalyst suffers a 52.5 % current lost. The superior stability of Cu clusters is ascribed to the strong S−Cu binding which can prohibit their agglomeration and dissolution under ORR conditions . Moreover, the fuel crossover effects of the Cu clusters and Pt/C catalysts were further examined by adding 1 mL of methanol to the electrocatalytic system (Figure S22).…”
Section: Resultsmentioning
confidence: 99%
“…41 Those Cu−O x /N y sites doping in graphitic carbon structures have shown excellent electrocatalytic ORR performance. 39 The exhibition of no Cu-based nanoparticles anchored in the graphitic carbon can be further confirmed by XRD results (Figure 2a), which only exhibit strong interplane diffraction of (002) at about 24.7°and the weaker diffraction of (101) at about 43.7°, corresponding to graphitic carbon. 32 The disorder degree and defects of the graphitic carbon structure in the prepared electrodes are investigated by Raman spectroscopy (Figure 2b).…”
Section: Resultsmentioning
confidence: 99%
“…They not only can be used as decent electrodes’ support for supercapacitors, lithium-ion batteries, and capacitive deionization but also exhibit superior electrocatalytic activity for O 2 , H 2 O, CO 2 , and N 2 . , Significantly, those high-performance electrocatalytic activities of biomassderived carbon mainly originate from suitable heteroatoms (such as N, S, O, or P) doped carbon structure, which can lead to the redistribution of local charge and spin in the sp 2 carbon lattice and destroy the initial electrical neutrality. Besides, it has been reported that an atomically dispersed metal–N x –C structure formed in biomassderived graphitic porous carbon is essential to the ORR and OER process because of it is high intrinsic catalytical performance sites. Although biomassderived carbon materials have so many advantages, their utilization as electrode still depends on a complicated coating route. How to directly transform rough biomass into flexible air electrodes with excellent mechanical properties and electrocatalytic activities is rarely reported.…”
Section: Introductionmentioning
confidence: 99%
“…Other PGM‐free catalysts, e.g., Co‐N‐C, Mn‐N‐C catalysts, etc., [ 7b,18c,67 ] have been proposed in literature to improve the stability because Fe is a typical Fenton reaction metal and catalyzes the formation of aggressive radicals. [ 68 ] The single‐atom Co‐N‐C catalyst produces abundant peroxide, [ 69 ] thus may participate in the Fenton reactions.…”
Section: Oxygen Reduction Reactionmentioning
confidence: 99%